Perbandingan Tingkat Kesegaran Jasmani Siswa Sekolah Menengah Atas Negeri 1 Sungai Beremas Kabupaten Pasaman Barat Dengan Siswa Sekolah Menengah Atas Negeri 11 Padang - mukhtadi radifan; ishak aziz (Jurusan Kepelatihan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2019)
The purpose of this study was to get a real picture of the level of physical fitness of each student in the school and at the same time to see the differences in the level of physical fitness of their students. This type of research is komperasi, with planning research